Analysis of Video Scribe Media of the Students Reading Interest in Indonesian Language Learning - Yani, Juli; Armayati, Leni; Hermaliza, Hermaliza; S, Ermawati; Ridwan, Ridwan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The aim of this research is to analyze Indonesian language learning media, find out how students are interested in reading, and the supporting and inhibiting factors for students' interest in reading. This type of research uses a qualitative descriptive method. The population of this study was class X at SMAN 1 Puloampel. Data collection techniques use observation, interviews and documentation techniques. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The research subjects were teachers and students of class X SMAN 1 Puloampel. After analyzing the research results, it shows that students' interest in reading has decreased due to several factors such as internal factors and external factors. The presence of Indonesian language learning media in the learning process can increase students' interest in reading and improve learning text procedures.